2023
DOI: 10.1007/s11356-023-26631-z
|View full text |Cite
|
Sign up to set email alerts
|

Resource productivity and environmental degradation in EU-27 countries: context of material footprint

Abstract: This study explores the relationship between the resource productivity and environmental degradation in European Union-27 countries. This study tests this relationship in context of high, moderate, and low material footprint sub-samples; these samples are formed utilizing the expectation–maximization machine learning algorithm. Using the panel data set of EU-27 countries from 2000 to 2020, linear and non-linear autoregressive distributed lag (ARDL) are applied for the symmetric and asymmetric evidence and to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 74 publications
0
0
0
Order By: Relevance
“…Leskosek (2012) found that social capital significantly mitigated illness-related poverty among households and that bridge-type social capital, associated with people of different socioeconomic statuses, had a more substantial impact on poverty alleviation than knot-type social capital, which is related to intra-family interactions [8]. In the context of COVID- [13][14][15][16][17][18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Leskosek (2012) found that social capital significantly mitigated illness-related poverty among households and that bridge-type social capital, associated with people of different socioeconomic statuses, had a more substantial impact on poverty alleviation than knot-type social capital, which is related to intra-family interactions [8]. In the context of COVID- [13][14][15][16][17][18].…”
Section: Literature Reviewmentioning
confidence: 99%